Silkworms, A Tool for the Preparation of Chloroplasts - Limaye, P.A.; Huddar, P.H.; Ghate, S.M. (Asian Journal of Chemistry, 2010)
The random separation of chloroplasts from the excreta of silkworms (Eri and Bombyx mori) was carried out at different stages. The same has been reported herewith.